Three-Dimensional Seepage Field Inversion Analysis and Seepage Control Effect Evaluation of Shuidishan Reservoir - PAN Yingjie; XU Jianjun; XIE Xinghua; LU Bin; ZHANG Yu; XIE Dongyi (Renmin Zhujiang)
Moderate permeable joint zones occur at the right dam abutment of the Shuidishan reservoir,which indicates a risk of seepage damage at the right dam abutment and its downstream.To reasonably evaluate the effect of reservoir seepage control measures,we build an overall three-dimensional (3D) seepage model to simulate the stable seepage in a natural state and the operation period.The permeability coefficient of the rock layer is optimized,and the seepage field characteristics of the reservoir area are analyzed.The results show that the downstream uplift pressure of the dam foundation is significantly reduced under the combined effect of the water-blocking curtain and the depressurization of drainage holes.Moreover,the curtain grouting lowers the local groundwater level within the right dam abutment,which inhibits the leakage of the joint zones to a certain extent.The overall seepage discharge of the reservoir is relatively small,which indicates that the layout of the water prevention and drainage system of the current project is acceptable,and thus the leakage of the joint zones at the right dam-abutment is effectively prevented.